2021
DOI: 10.18502/acta.v58i12.5154
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features and Clinical Study of Kawasaki Disease in Iran

Abstract: Kawasaki disease (KD) is an acute febrile systemic vasculitis of unknown etiology and the major cause of pediatric acquired cardiac disease worldwide, particularly in developed countries. This study characterizes the epidemiologic and clinical features of KD in the Pediatric Rheumatology Department service in a general hospital. 120 patients with the diagnosis of KD between 1990 and 2009 were enrolled. We investigated the epidemiologic and clinical features of coronary artery involvement of the patients. Frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…| 3 of 8 Gender as a neonatal factor has been reported to have a significant effect on the type and presence of CHD so it can be considered a risk factor. 22,23 Our results show that the ratio of male to female neonates is 2.6, which means that CHD is more prevalent in male infants. The prevalence of male patients ranged from 45% to 73% of all conditions in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…| 3 of 8 Gender as a neonatal factor has been reported to have a significant effect on the type and presence of CHD so it can be considered a risk factor. 22,23 Our results show that the ratio of male to female neonates is 2.6, which means that CHD is more prevalent in male infants. The prevalence of male patients ranged from 45% to 73% of all conditions in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…15 A retrospective study done by Akbariasbagh et al from Iran found overall prevalence of cardiovascular anomalies among IDMs as 30% which is higher than what was noted in this study (20.0%). 16 Dimitriu et al shared that cardiac abnormalities were noted in 23% of the IDMs, without being affected by pulmonary hypertension and HCM. 17 Schafer et al mentioned in their study that the occurrence of cardiovascular anomalies among all other anomalies was 37.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Babies exposed to maternal hyperglycemia have an increased risk of congenital heart structural anomalies, heart morphological changes and dysfunction, including congenital heart disease, [1][2][3] cardiac hypertrophy in embryonic hearts, 4 impaired cardiac diastolic function in the fetuses 5 and early-onset cardiovascular disease in childhood or early adulthood. 6 However, the molecular mechanisms responsible for the disruption of normal heart development in the offspring of mothers with diabetes have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%